Targeting PARP1 by Small Molecule Drugs for the Therapeutics of Gynaecological Cancers - Alalawy, Adel I. (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: In gynaecological cancers like ovarian, endometrial, and cervical cancer, where DNA damage repair mechanisms are frequently dysregulated, targeting PARP1 offers a targeted therapeutic approach. Materials and Methods: This study was aimed to identify the small molecules for the inhibition of PARP1 using bioinformatics and in vitro methods. Screening and molecular docking of a diverse ligand library identified Apigenin as a potential Results: PARP1 inhibitor, exhibiting strong binding affinity of -9.0 kcal/mol for the PARP1. Further analysis via SwissTargetPrediction revealed diverse biological activities associated with Apigenin, indicating its therapeutic potential. Additionally, time-dependent cytotoxicity assays demonstrated Apigenin's negligible effect on non-cancerous cells (HEK-293), affirming its safety profile. Moreover, relative mRNA expression studies in Apigenin-treated HeLa-229 cells revealed a significant decrease in PARP1 expression, suggesting its inhibitory effect on cancer-related pathways. Conclusion: Overall, these findings highlight Apigenin as a promising therapeutic cause for targeting PARP1 in cancer treatment, underscoring its potential for further preclinical and clinical investigations.
Keywords: Apigenin; Gynaecological Cancers; HeLa-229; Molecular Docking; PARP1; Inhibition